Tithe Barn at Bradford on Avon - Saint Aldhelm
the structural quality of this timbered roof, which still retains most of its original material, is similar to those of manor house and parish church. Much domestic building was also in timber, which, with its limited life, has not survived. Its use or large structures accentuated the possibilities of framed construction, where the loads are carried by long structural members, which support a lighter infilling to keep out the weather.